Wide Sargasso Sea [videorecording] - Maher, Brendan, director 561258 ([United States] : Acorn Media, 2006)
Adapted from Jean Rhys' award-winning novel, this is a prequel to Charlotte Bronte's Jane Eyre and paints a rather different story of Mr. Rochester's first wife. Set in lush 19th century Jamaica, this is the story of the relationship between a passionate Creole heiress, Antoinette, and a brooding Englishman, Edward Rochester.